Analisis Pengembangan Objek Wisata melalui Kearifan Lokal untuk Meningkatkan Kesejahteraan dan Perekonomian Masyarakat di Desa Wisata Kampung Bekelir Tangerang - Triandi Pradana (Publikasi Indonesia, 2022)
The existence of the colorful houses of Kampung Bekelir has now grown the public's perspective on the tourism sector. Even this is based on the potential of a building that was originally ordinary and even classified as very dirty and then changed by providing various attractive colors to become tourist attractions in the form of photos. Then it was added with the conversion of the banks of the Cisadane River into culinary stalls for UMKM residents of Kampung Bekelir. The residents of Bekelir feel an increase in the economy from the existence of this Firm Village, because residents can sell the products they make and culinary delights for tourists to earn additional income. At first, these UMKM became a source of additional income, now they are the main source of income for the residents of Bekelir.